Case report: Pheochromocytoma-induced pseudo-Cushing’s syndrome - Bobrowicz, Małgorzata; Nagórska, Anna; Karpiłowska, Anna; Rosłon, Marek; Hubska, Joanna; Gładka, Adrianna; Toutounchi, Sadegh; Koperski, Łukasz; Ambroziak, Urszula (Frontiers in Endocrinology, 2024)
Non-neoplastic hypercortisolaemia, also known as pseudo-Cushing’s syndrome (PCS), is a physiological overactivation of the hypothalamic–pituitary–adrenal axis that can be triggered by conditions such as depression, eating disorders, extreme exercise, obesity, alcoholism, poorly controlled diabetes, chronic kidney disease, and cachexia. Here, we describe an unusual case of pheochromocytoma-induced PCS. A 66-year-old woman was referred to the hospital due to pronounced weakness, loss of appetite, apathy, weight loss, newly diagnosed diabetes mellitus, and poorly controlled hypertension. The biochemical evaluation suggested ACTH-dependent hypercortisolemia with severe hypokalemia, metabolic alkalosis, and hyperglycemia. Markedly elevated levels of metanephrines, along with imaging showing a heterogeneous adrenal lesion, provided evidence for pheochromocytoma. Considering the clinical features and the results of laboratory and imaging tests, there was a suspicion of hypercortisolemia due to ectopic ACTH secretion by a pheochromocytoma. The patient underwent adrenalectomy following pre-treatment with doxazosin and metyrapone, enteral feeding, protein supplementation, and insulin administration. Post-surgery, the patient did not require further antidiabetic medication, experienced gradual weight gain, improved well-being, and did not need glucocorticoid supplementation. Histopathological examination confirmed a pheochromocytoma; however, both anti-ACTH and anti-CRH stainings were negative, leading to a diagnosis of PCS. This case highlights the distinctive presentation of PCS caused by pheochromocytoma, as demonstrated through clinical, laboratory, and histopathological findings, and emphasizes the successful resolution achieved through adrenalectomy and supportive care.